Potential therapeutic effect of low-dose paclitaxel in melanoma patients resistant to immune checkpoint blockade: a pilot study - Gebhardt, Christoffer; Simon, Sonja C. S.; Bitsch, Rebekka; Gries, Mirko; Mun, Dong Hun; Reinhard, Raphael; Holland-Letz, Tim; Umansky, Viktor; Utikal, Jochen (Cellular immunology, 2021)
The low dose application of chemotherapeutic agents such as paclitaxel was previously shown to initiate anti-tumor activity by neutralizing myeloid-derived suppressor cells (MDSCs) in melanoma mouse models. Here, we investigated immunomodulating effects of low-dose paclitaxel in 9 metastatic melanoma patients resistant to prior treatments. Three patients showed response to therapy (two partial responses and one stable disease). In responding patients, paclitaxel decreased the frequency and immunosuppressive pattern of MDSCs in the peripheral blood and skin metastases. Furthermore, paclitaxel modulated levels of inflammatory mediators in the serum. In addition, responders displayed enhanced frequencies of tumor-infiltrating CD8+ T cells and their activity indicated by the upregulation of CD25 and TCR ζ-chain expression. Our study suggests that low-dose paclitaxel treatment could improve clinical outcome of some advanced melanoma patients by enhancing anti-tumor immunity and might be proposed for combined melanoma immunotherapy.
Available online 28 December 2020
Gesehen am 30.11.2021